Why Did Developers Migrate Android Applications From Java to Kotlin? - Martinez, Matias; Gois Mateus, Bruno (IEEE transactions on software engineering, 2022)
Currently, the majority of apps running on mobile devices are Android apps developed in Java. However, developers can now write Android applications using a new programming language: Kotlin, which Google adopted in 2017 as an official programming language for developing Android apps. Since then, Android developers have been able to: a) start writing Android applications from scratch using Kotlin, b) evolve their existing Android applications written in Java by adding Kotlin code (possible thanks to the interoperability between the two languages), or c) migrate their Android apps from Java to Kotlin. This paper aims to study this last case. We conducted a qualitative study to find out why Android developers have migrated Java code to Kotlin and to bring together their experiences about the process, in order to identify the main difficulties they have faced. To execute the study, we first identified commits from open-source Android projects that have migrated Java code to Kotlin. Then, we emailed the developers that wrote those migrations. We thus obtained information from 98 developers who had migrated code from Java to Kotlin. This paper presents the main reasons identified by the study for performing the migration. We found that developers migrated Java code to Kotlin in order to access programming language features (e.g., extension functions, lambdas, smart casts) that are not available with Java for Android development, and to obtain safer code (i.e., avoid null-pointer exceptions). We also identified research directions that the research community could focus on in order to help developers to improve the experience of migrating their Java applications to Kotlin.